Sexual dimorphism in species of Schistura (Teleostei: Nemacheilidae) from the Mae Khlong basin and peninsular Thailand - Plongsesthee, Rungthip; Beamish, F. William H.; Page, Lawrence M. (Zootaxa, 2012)
Sexually dimorphic characteristics are described for four species of Schistura from the Mae Khlong basin and peninsularThailand. Males of S. mahnerti have a suborbital flap and rows of unculi on the upper surfaces of the pectoral-fin rays.Females of S. mahnerti have a suborbital groove. None of the morphological measurements differ significantly betweenmales and females of S. mahnerti. In the other three species, S. aurantiaca, S. cf. aurantiaca, and S. sexcauda, all indi-viduals lack the flap or groove, but most males have a conspicuous black botch on the procurrent rays of the upper lobeof the caudal fin, a feature absent in most females. Some morphometric characteristics vary between sexes of these spe-cies. Sexually dimorphic traits presumably have a function related to reproduction; however, little is known about reproduction in Schistura, and variation in morphology in relation to habitat or other environmental factors has not been studied.